The photographer's portfolio development workshop - Neill, William (Rocky Nook Inc., 2022)
Once a photographer has learned the fundamental techniques of photography--the basics of exposure, composition, and focus--their work often improves over the course of a few months or years. The world is full of wonders to photograph, and photographers can be pulled in many directions, excitedly chasing the light and the moment. This approach can certainly yield wonderful photographs, but over time the photographer's progress often begins to slow, and eventually, it can stop altogether. The reason for this is simple: creativity begins with image-making, but true progress comes with learning to edit and organize your work in ways that reflect your unique style and perspective, ways that offer you insight into how you can improve your work moving forward. In short, the key to becoming the best photographer you can be is to create an ongoing portfolio (or multiple portfolios) of your work. Based on an eight-week course taught by renowned photographer and author William Neill, The Photographer's Portfolio Development Workshop provides the tools and skills you need in order to create a methodology that allows you to create a tightly edited portfolio of work, no matter your end goal: a box of prints, a book, an online presentation or website, or even a gallery exhibit. A portfolio is simply a collection of photographs with a consistent theme and consistent quality. In developing such a body of work, you will learn what your specific passions are, find focus for your work, and begin the iterative process of creating better and better photographs over time. By constantly working within a "feedback loop"--where you carefully assess and edit your images, note and learn from mistakes, then go out and create more photographs--you'll develop a portfolio that is constantly gaining in strength, quality, and impact. It's no surprise that you'll also become a much better photographer. No matter the photographic genre you work in, this book will teach you to objectively assess your work on both technical and aesthetic levels, establish a personal standard of quality, focus your efforts on new work, and become a better photographer. The book features eight lessons, along with assignments at the end of each lesson to propel you and your work forward. Throughout, Neill uses his own photographs to illustrate the process he has used for years to create multiple portfolios and books.